1973
DOI: 10.1128/jb.115.3.1094-1102.1973
|View full text |Cite
|
Sign up to set email alerts
|

tyrR, A Regulatory Gene of Tyrosine Biosynthesis in Salmonella typhimurium

Abstract: 4-Fluorophenylalanine-resistant mutants of Salmonella typhimurium were isolated in which tyrosine pathway enzymes were not repressed by L-tyrosine. The mutants produced elevated levels of 3-deoxy-D-arabinoheptulosonic acid 7-phosphate (DAHP) synthetase (tyr) and chorismate mutase T-prephenate dehydrogenase, and these enzymes as well as transaminase A were not repressed by high concentrations of tyrosine. Genetic analysis revealed that a mutation in a gene designated tyrR was responsible for the constitutivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1975
1975
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In wild-type Salmonella, tyrosine-inhibitable DAHP synthase accounts for approximately 10% of total DAHP synthase activity (11). In the operator-constitutive mutant SG12 grown at 250C (13), activity of DAHP synthase is twice as high as found at 37°C (10), and activity of DAHP synthase (tyr) is 85% of the total ( Table 1). The levels obtained were about 35-fold higher than in wild-type cells grown in minimal medium and approximated those of DAHP synthase (phe) found by Simpson et al (23) structural gene for the phenylalanine isoenzyme into the genome of specialized transducing phage lambda.…”
Section: Discussionmentioning
confidence: 89%
“…In wild-type Salmonella, tyrosine-inhibitable DAHP synthase accounts for approximately 10% of total DAHP synthase activity (11). In the operator-constitutive mutant SG12 grown at 250C (13), activity of DAHP synthase is twice as high as found at 37°C (10), and activity of DAHP synthase (tyr) is 85% of the total ( Table 1). The levels obtained were about 35-fold higher than in wild-type cells grown in minimal medium and approximated those of DAHP synthase (phe) found by Simpson et al (23) structural gene for the phenylalanine isoenzyme into the genome of specialized transducing phage lambda.…”
Section: Discussionmentioning
confidence: 89%
“…The results shown in Fig. 1C indicated that this gene is the S. typhimurium homolog of tyrR (90% identity over 30 amino acids), a regulator of aromatic amino acid biosynthesis and transport (15,26).…”
mentioning
confidence: 91%
“…Some of the thiE, F mutants mapped in this general region (Gots, personal communication) may be homologous to thiB. A single transducing fragment carries phe and tyr (213), as well as aroF and tyrO (formerly fpr) (109). The gene pyrG is jointly transduced with cysCD (25).…”
mentioning
confidence: 99%